Paraurethral leiomyoma in a woman: a case report - Coumary A, Sendhil; Ghose, Seetesh; Samal, Rupal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Paraurethral leiomyomas are rare, benign smooth muscle tumours of the urogenital tract. Most para-urethral tumours occur in the reproductive age group. Its etiology is uncertain and its presentation is variable. Here we present a 45 year old multiparous lady, who approached the out-patient department, with complaints of profuse foul-smelling discharge and a mass per vaginum for 10 days.